2017
DOI: 10.1002/ecy.1957
|View full text |Cite
|
Sign up to set email alerts
|

Predator ontogeny affects expression of inducible defense morphology in rotifers

Abstract: Abstract. Many prey organisms show induced morphological responses to predators including changes in protective spine length, such as in rotifers, although previous studies have mainly focused on how prey become larger than the predator gape-size optimum. Here we show that a large-sized predator makes prey rotifers escape below the gape-size optimum of the predator by reducing spine length. In experiments and field studies we show that during part of their ontogeny fish larvae feed intensively on the common ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 43 publications
5
13
0
Order By: Relevance
“…neck teeth, a higher helmet, or a longer shell spine), reducing the probability of the predator to capture and ingest the prey (Laforsch & Tollrian, 2004; Tollrian & Dodson, 1999) and changes in behaviour, such as diel vertical migration, that reduces the probability of encounters between predator and prey (De Meester et al., 1999). With respect to aquatic rotifers, more studies on predator‐induced defences have investigated morphological defences (Gilbert, 1999, 2013; Zhang, Brönmark, et al., 2017; Zhang, Hollander, et al., 2017), although behavioural responses are potentially more rapid and efficient.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…neck teeth, a higher helmet, or a longer shell spine), reducing the probability of the predator to capture and ingest the prey (Laforsch & Tollrian, 2004; Tollrian & Dodson, 1999) and changes in behaviour, such as diel vertical migration, that reduces the probability of encounters between predator and prey (De Meester et al., 1999). With respect to aquatic rotifers, more studies on predator‐induced defences have investigated morphological defences (Gilbert, 1999, 2013; Zhang, Brönmark, et al., 2017; Zhang, Hollander, et al., 2017), although behavioural responses are potentially more rapid and efficient.…”
Section: Introductionmentioning
confidence: 99%
“…To cope with predators with different kinds of hunting and feeding techniques, rotifers have evolved various anti‐predator strategies, including both changes in morphology (Gilbert, 2013) and behaviour (Gilbert, 2014, 2018). More than 14 rotifer species have been reported to exhibit predator‐induced morphological defences by increasing or decreasing spine length (Gilbert, 2017; Yin et al., 2017; Zhang, Brönmark, et al., 2017; Zhang, Hollander, et al., 2017). In addition to morphological defences, rotifers have developed various behavioural defence strategies, including diel vertical migration (Gilbert & Hampton, 2001), epizoic behaviour (Gilbert, 2014, 2018; Iyer & Rao, 1995), and escape or evasive behaviours (Gilbert, 1987; Gilbert & Kirk, 1988; Gilbert & Williamson, 1978) in order to reduce risk from predators or interference competitors.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, while the enhanced spine development described above (which is the subject of this review) is the normal response in brachionid rotifers to Asplanchna and other invertebrate predators (Table ), the interaction of these prey with planktivorous fish can produce the opposite effect, a reduction in spine length. Zhang et al () found that Keratella cochlearis decreased the length of its posterior spine in response to kairomones from larval fish ( Rutilus rutilus ), which reduced its vulnerability to this size‐selective predator.…”
Section: Predator‐induced Morphological Responsesmentioning
confidence: 99%
“…Environmental costs, which are occasional costs that are expressed only under certain environmental conditions, may be more likely to influence spine induction in these animals. For example, the presence of long spines may reduce the rotifer's fitness in the presence of certain predators (Zagarese and Marinone ; Zhang et al ) or competitors (Aránguiz‐Acuña et al ). In Daphnia , on the other hand, costs have been more conspicuous, although not always clearly present.…”
Section: Predator‐induced Spine Development In Brachionid Rotifers Kmentioning
confidence: 99%
“…Laboratory assays revealed that various environmental factors affected the morphological characters of rotifers, such as food type 5 , food quality 6 and food density 7 , temperature 8 , salinity 4 , desiccation 9 , 10 and predation 11 , 12 . Generally, the morphological variations are adaptive responses to environmental changes.…”
Section: Introductionmentioning
confidence: 99%